New lichen records from Turkey - Yazici, Kenan; Aslan, Ali; Aptroot, André (Bangladesh Journal of Plant Taxonomy, 2013)
Three lichen species, namely Cladonia grayi G. Merr. ex Sandst., Pertusaria subventosa Malme var. subventosa, and Parmelia squarrosa Hale are reported as new to Turkey as a result of a lichenological survey in the Burdur region of the country. Descriptions are presented, including geographic distribution, substrate, chemistry, and comparisons with morphologically similar taxa. DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17395 Bangladesh J. Plant Taxon. 20(2): 207-211, 2013